Impact and Enablers of Pharmacogenetic-Informed Treatment Decisions—A Longitudinal Mixed-Methods Study Exploring the Patient Perspective - Bollinger, Anna; Semedo Fortes, Melissa; Meyer zu Schwabedissen, Henriette E.; Hersberger, Kurt E.; Stäuble, Céline K.; Allemann, Samuel S. (Pharmacy, 2025)
Pharmacogenetic (PGx) testing is a promising approach for optimizing drug therapies. However, there is limited knowledge regarding its real-world utilization and long-term impact in clinical practice. This study assessed how often PGx information informs treatment decisions and evaluated patients’ perspectives on its use and non-use, identifying enablers for PGx implementation. A mixed-methods study was conducted with 24 patients with a median of 1 year after PGx testing. Medication and health-related data were collected at enrollment and at the follow-up 1 year later using a semi-structured questionnaire. At the follow-up, 62 medication changes were identified in 18 patients. A median of four medication changes per patient were initiated mainly by medical specialists (58%). PGx information was considered for 15 patients in 39 medication changes (63%). Patient-reported factors contributing to the non-use of PGx information included a lack of knowledge and interest among healthcare professionals (HCPs), structural and administrative barriers, and an over-reliance on patient advocacy. Potential enablers should address targeted PGx education, interprofessional collaboration, awareness among policymakers, and concise recommendations focused on PGx-actionable drugs from testing providers. By implementing these interdependent enablers, PGx can evolve into a long-term, clinically integrated cornerstone of individualized pharmacotherapy.